Aplicação da regra de decisão empresarial ao administrador da sociedade limitada sob o enfoque da boa-fé privada e dever de fidúcia - Silva, Aline Fonseca da (2023)
The subject’s purpose is verify the feasibility of applying the business decision rule stipulated in paragraph 6 of article 159 of the Corporations Law to the limited liability companies, in the event of breach of fiduciary duties of diligence and loyalty. The work is restricted to the structuring of the limited liability company composed of two partners and managers. Although there are some controversial doctrinal issues regarding the supplementary application of the anonymity law to limited liability companies, the possibility of such an application was considered, although the need for a general meeting to bring a corporate action against a defaulting partner was not considered. A search in comparative law was conducted as to the origins of the fiduciary duties that permeate the relations of the of the Corporations Law to the limited liability companies, in the event of breach of fiduciary duties of diligence and loyalty. The doctrinal and jurisprudential construction of the business judgment rule was deepened. The dissertation also demonstrates the criteria of applicability of the business judgment rule by the Superior Court of Justice and the São Paulo State Court of Justice. The final proposal is, after analyzing the decisions, to detect the minimum judicial intervention in corporate decisions, maintaining the discretion of managers to act in the company's business, except in cases in which there is a blatant violation of corporate duties, for which the rule provided in paragraph 6 of Article 159 of the Corporations Law will apply.